2022
DOI: 10.56556/jtie.v1i1.142
|View full text |Cite
|
Sign up to set email alerts
|

Using Science, Technology, and Innovation (Sti); in Achieving Sustainable Development in Developing Countries (Dcs)

Abstract: University-industry relations need to be strengthened; several institutions have technology transfer offices that assist in the formation of spin-off companies. On inventions and technologies, different commercialization routes, the functions of technology transfer offices, and diverse organizational structures will be examined. By showing current innovation and technology, this paper contributes to attaining sustainable development for developed nations by academic and agricultural industry report, developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…They adopted Scopus database and text mining program VantagePoint to identify 425 records and finally found that 83% of them suggested an increasing trend of water recycling economy. A study by Maiwada and Ahmad 9 contributed to realizing lasting development in developed countries through academic and agricultural industry reports, development and commercialization operations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They adopted Scopus database and text mining program VantagePoint to identify 425 records and finally found that 83% of them suggested an increasing trend of water recycling economy. A study by Maiwada and Ahmad 9 contributed to realizing lasting development in developed countries through academic and agricultural industry reports, development and commercialization operations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Technological progress is closely related to a country's economic growth and social progress (Maiwada, 2022;Y. Y. Zhang et al, 2021), but as environmental problems become increasingly prominent in the process of economic growth, some studies have paid increasing attention to the relationship between economic growth and environmental pollution (Adebanjo & Shakiru, 2022) and focused on the impact of technological progress on sustainable development (Bakare & Okuonghae, 2022;Dar & Ahmad, 2022;Maiwada & Jamoh, 2022), carbon emissions (L. Huang et al, 2017;Kang et al, 2018) and renewable energy consumption (Jiang & Khan, 2023). However, their findings are not uniform; L. Huang et al (2017) find that intermediate goods imports, independent research and development (R&D), and imitative innovation significantly reduce the implied carbon emission intensity of China's manufacturing exports, but Jiang and Khan (2023) find that technological innovation increases CO2 emissions and renewable energy consumption.…”
Section: Technological Progress Pathmentioning
confidence: 99%
“…Technological progress is closely related to a country’s economic growth and social progress (Maiwada, 2022; Y. Y. Zhang et al, 2021), but as environmental problems become increasingly prominent in the process of economic growth, some studies have paid increasing attention to the relationship between economic growth and environmental pollution (Adebanjo & Shakiru, 2022) and focused on the impact of technological progress on sustainable development (Bakare & Okuonghae, 2022; Dar & Ahmad, 2022; Maiwada & Jamoh, 2022), carbon emissions (L. Huang et al, 2017; Kang et al, 2018) and renewable energy consumption (Jiang & Khan, 2023).…”
Section: Literature Review and Summarymentioning
confidence: 99%
“…In this context, a study by Modi et al (2022) confirmed that the growth of the size of the yard positively affects the rise in air temperature, the average radiant temperature in the place and the physiological temperature. Dar and Ahmad (2022) and Maiwada and Jamoh (2022) suppose that technology (technology mobile as example) was an essential element to realize sustainable development goals. Among these goals, technology can develop and save the environment.…”
Section: Literature Reviewmentioning
confidence: 99%